2006
DOI: 10.1158/1541-7786.mcr-06-0204
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Oncoprotein Functions in Activation of Fibroblast Growth Factor Receptor Signaling

Abstract: Activation of the fibroblast growth factor (FGF) receptor 3 (FGFR3) has been linked to the development of human cancers by mechanisms that are not well understood. The MUC1 oncoprotein is aberrantly overexpressed by certain hematologic malignancies and most human carcinomas. The present studies show that MUC1 associates with FGFR3. Stimulation of cells with FGF1 increased the interaction between MUC1 and FGFR3. FGF1 stimulation also induced c-Src-dependent tyrosine phosphorylation of the MUC1 cytoplasmic domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 57 publications
2
82
0
Order By: Relevance
“…Classically, activation of IGF-1R results from direct binding of the ligand IGF-1, leading to a downstream signaling cascade. A very interesting clue is that MUC1 directly interacts with growth factor receptors, including the endothelial growth factor receptor (Pochampalli et al, 2007b), transforming growth factor-a receptor (Pochampalli et al, 2007a) and fibroblast growth factor receptor (Ren et al, 2006). Results from this study confirm that MUC1 is an important regulator of IGF-1R activation during tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…Classically, activation of IGF-1R results from direct binding of the ligand IGF-1, leading to a downstream signaling cascade. A very interesting clue is that MUC1 directly interacts with growth factor receptors, including the endothelial growth factor receptor (Pochampalli et al, 2007b), transforming growth factor-a receptor (Pochampalli et al, 2007a) and fibroblast growth factor receptor (Ren et al, 2006). Results from this study confirm that MUC1 is an important regulator of IGF-1R activation during tumor angiogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, recent findings have revealed that diverse carcinoma cells express the MUC1-C in mitochondria or in the nucleus in association with the Wnt effector h-catenin (25)(26)(27)(28)(29). MUC1 interacts with members of the ErbB family of receptor tyrosine kinases and with the fibroblast growth factor receptor 3 (26,30,31). Stimulation of such receptors induces c-Src-dependent tyrosine phosphorylation of the MUC1-CD on a YEKV motif and thereby results in nuclear localization of MUC1 and h-catenin or heat shock protein (Hsp) 90-mediated targeting of MUC1 to mitochondria (25,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…MUC1 engages in signal transduction through MUC1-ND-mediated ligand-binding (39,42,43) or by interacting with receptors for growth (34,40) and differentiation factors (10 -12), which contributes to the growth and survival of cancer cells. With respect to invasion and metastasis, its molecular role has not been clarified.…”
Section: Discussionmentioning
confidence: 99%